Analysis of Dialectal Differences Between Saudi Arabian and Egyptian 'Ammiya Arabic - Anshori, Rodli Al; Ikhsan, Arief Maulana; Wafa, Muhammad Azka Shidqul; Mustofa, Syaiful; Albudaya, Yasser Abdullah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
Dialects are ways of speaking for small groups of people within a larger language community using a particular language. Geographical and anthropological differences cause the emergence of dialects. What distinguishes it is the change of letters, pronunciation deviations, and changes in harakat on several letters in one word or even entirely. The purpose of this study is to analyze the differences in dialects of Arabic ‘Ammiya Saudi Arabia and Arabic ‘Ammiya Egypt. This research method uses a qualitative approach. the type of research is Library Research. The data analysis is descriptive-analytical. The writing uses the deductive method. The results showed that the differences in Saudi Arabia and Egyptian Arabic dialects are in two aspects; Phonological and Morphological. In the phonological aspect occurs in the alternation of sounds, the addition of sounds, and the elimination of sounds. In the Morphological aspect, there are differences in the word formula (wazan).